An Errors Analysis in Using Diathesis (態) in Written Text of Japanese Language Department Senior Students at Universities in Medan - Murniati Br. Barus; Mhd. Pujiono (IZUMI, 2021)
The grammatical category that shows the relationship between the subject is diathesis. From the researcher’s observations, it was found that Japanese students used diathesis errors in the city of Medan. Therefore, this study discusses what forms of errors are and how Japanese universities students in Medan make the error in using diathesis forms. The specific purpose of this study is to analyze and determine the forms and patterns of errors in using the diathesis (態/tai) that it becomes a consideration for Japanese language lecturers to provide more effective teaching for Japanese learners, especially universities students in Medan. The types of diathesis sentences analyzed are judoutai (passive diathesis), Shieki (causative), kiboubun (wish form), and jujubun (expression of give-take). This research is descriptive qualitative research with error analysis. The data were sentences using diathesis (tai), sourced from written text made by 30 senior students of the Japanese department at the Universitas Sumatera Utara and the Universitas Harapan Medan. In conclusion, the form of error has been found in passive (受 身), a causative (使役), and the expression of the give-take action (授受表現) diathesis, which is realized grammatically and lexically. Errors include changing verbs, using particles (joshi), and assigning word unit functions to sentences. This study concludes that understanding and practice on the ukemi, shieki, and jujubun diathesis is needed in Japanese language learning among university students in Medan to improve student skills